Ghalib : selected poems and letters - Pritchett, Frances W., 1947-; Cornwall, Owen T. A. (New York : Columbia University Press, 2017)
This selection of poetry and prose by Ghalib provides an accessible and wide-ranging introduction to the preeminent Urdu poet of the nineteenth century. Ghalib's poems, especially his ghazals, remain beloved throughout South Asia for their arresting intelligence and lively wit. His letters--informal, humorous, and deeply personal--reveal the vigor of his prose style and the warmth of his friendships. These careful translations allow readers with little or no knowledge of Urdu to appreciate the wide range of Ghalib's poetry, from his gift for extreme simplicity to his taste for unresolvable complexities of structure. Beginning with a critical introduction for nonspecialists and specialists alike, Frances Pritchett and Owen Cornwall present a selection of Ghalib's works, carefully annotating details of poetic form. Their translation maintains line-for-line accuracy and thereby preserves complex poetic devices that play upon the tension between the two lines of each verse. The book includes whole ghazals, selected individual verses from other ghazals, poems in other genres, and letters. The book also includes a glossary, the Urdu text of the original poetry, and an appendix containing Ghalib's comments on his own verses.
Frontmatter -- Contents -- Acknowledgments -- Introduction: Ghalib's Life and Times -- Part One: Ghazals -- Part Two: Ghazal Verses -- Part Three: Other Genres -- Notes -- Appendix 1. Ghalib's Comments on His Own Verses -- Appendix 2. Ghalib Concordance, with Standard Divan Numbers -- Glossary of Technical Terms and Proper Names -- Bibliography -- Index -- Urdu Text.
Print version record.
In English.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Ghalib, Mirza Asadullah Khan, -- 1797-1869 -- Translations into English; Ghalib, Mirza Asadullah Khan, -- 1797-1869 -- Correspondence; Ghalib, Mirza Asadullah Khan, -- 1797-1869; Urdu poetry -- Translations into English; Electronic books; Livres numériques.; e-books.; RELIGION -- Islam -- General; Urdu poetry; Electronic books; poetry; Poetry; Personal correspondence; Translations; Poetry; Poésie.